(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
This article has no abstract. The first 100 words appear below: A 50-year-old female, hailing from Patuakhali, was admitted at the Department of Ophthalmology for the management of severe reduction of vision and pain at the right eye for the last 7 months following cataract surgery at a government hospital. Her cataract surgery (small incision cataract surgery with PC-IOL implantation) of the right eye was performed on October 28, 2018. On the first post-operative day, she developed pain, redness and severe reduction of vision in the right eye. The following day, she was discharged with the advice of some medications like moxifloxacin, dexamethasone, bromfenac eye drops and oral acetazolamide and potassium.